1995
DOI: 10.1210/jcem.80.2.7531713
|View full text |Cite
|
Sign up to set email alerts
|

H19 and insulin-like growth factor-II gene expression in adrenal tumors and cultured adrenal cells.

Abstract: The expression of H19 and insulin-like growth factor-II (IGF-II) genes is important for fetal growth, and the misexpression of these genes may also be involved in the development of some tumors. In human fetal adrenals, H19 and IGF-II expression levels are very high. We show here that H19 is strongly expressed (approximately 50% of the expression in fetal adrenals and 6-fold higher than that in adult liver) in normal adult adrenals (n = 9), adrenocortical adenomas (n = 28), and hyperplastic adrenals (n = 11). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 15 publications
2
39
0
2
Order By: Relevance
“…To avoid interferences, genotoxic effect was quantitatively expressed as induction ratios (IRs), which were calculated for each dose as the ratio of ␤-galactosidase activity in a sample to the solvent control. IRs above 2.0 were interpreted as sufficient positive results if they had a reproducible dose-response curve, whereas those below 2.0 were interpreted as negative results [28]. Ames assays were performed according to the standard plate incorporation method with S. typhimurium classical strains TA98 and TA100, which are capable of detecting base frameshift type and base pair substitution-type mutagenicity, respectively [29].…”
Section: Mutagenicity Assessmentmentioning
confidence: 99%
“…To avoid interferences, genotoxic effect was quantitatively expressed as induction ratios (IRs), which were calculated for each dose as the ratio of ␤-galactosidase activity in a sample to the solvent control. IRs above 2.0 were interpreted as sufficient positive results if they had a reproducible dose-response curve, whereas those below 2.0 were interpreted as negative results [28]. Ames assays were performed according to the standard plate incorporation method with S. typhimurium classical strains TA98 and TA100, which are capable of detecting base frameshift type and base pair substitution-type mutagenicity, respectively [29].…”
Section: Mutagenicity Assessmentmentioning
confidence: 99%
“…Expression of H19 RNA also inhibited soft agar growth and tumorigenicity in some, but not all, transfected cancer cells (Hao et al, 1993;Isfort et al, 1997), so a possible trans-acting function of the RNA deserves future scrutiny. H19 is silenced, either by de novo DNA hypermethylation of the maternal allele and immediate upstream DNA, or by loss of this allele, in most Wilms' tumors and in several other embryonal neoplasms (Moulton et al, 1994;Steenman et al, 1994;Liu et al, 1995;Taniguchi et al, 1995;Casola et al, 1997;Fukuzawa et al, 1999). Biallelic methylation of H19, associated with relaxation of IGF2 imprinting, is also observed in a specific subset of cases of classical BWS (Catchpoole et al, 1997) with a high predisposition to Wilms' tumor (Engel et al, 2000;Weksberg et al, 2001;DeBaun et al, 2002), and in a related BWS-like overgrowth disorder, also with a predisposition to Wilms' tumor (Morison et al, 1996).…”
Section: Imprinted Genes Expressedmentioning
confidence: 99%
“…1,7,59 -61 A number of growth factors, such as insulin-like growth factor (IGF)-I and -II, epidermal growth factor (EGF), insulin, tumor necrosis factor (TNF)-␣, interferon (IFN)-␥, and transforming growth factor (TGF)-␤1, and activators or inhibitors of protein kinase A and C modulated the H19 gene expression level in different cell lines: vascular smooth muscle cells, 10 fetal adrenal cells, 62 and cultured adrenal cells. 47 Otherwise, Leibovitch et al 63 reported that the overexpression of c-mos protein in the muscle cell line C2C12 induces a concomitant increase of H19 RNA expression, suggesting an interrelationship between these two gene products during muscle differentiation.…”
mentioning
confidence: 99%